THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1946)
Abstract If an example were sought from accounting to show that living language changes, the word "surplus" would be a good one to use. It was not originally a bookkeeping term, having come rather late into accounting from earlier use in law. Its antecedent in bookkeeping was profit. But before the noun "surplus" became as prominent in accounting as is the noun "profit," it passed through a long chrysalid stage in law as an adjective in the phrase "surplus profits." After the middle of the nineteenth century the term "surplus assets" appears in court cases, especially cases in Great Britain. In 1869 "whole surplus" was used in referring to assets of an enterprise in dissolution. Surplus assets, it was said, must be distributed pro rata. In 1889 the courts referred to dividing the surplus after payment of liquidation expenses. In 1896 a court tried to link the two terms by saying that surplus assets means surplus profits, and then explained that surplus assets are those remaining after payment of debts and recoupment of capital. It was perhaps not well understood until more recently that the word "profits" always carries within it a reference to "surplus assets," but that the phrase "surplus assets" does not always connote "profits."